2022
DOI: 10.3389/fonc.2022.860475
|View full text |Cite
|
Sign up to set email alerts
|

Markers Associated With Tumor Recurrence in Patients With Breast Cancer Achieving a Pathologic Complete Response After Neoadjuvant Chemotherapy

Abstract: BackgroundPatients who achieve a tumor pathologic complete response (pCR) after neoadjuvant chemotherapy (NAC) have better outcomes than patients with residual tumor. However, tumors still recur in the pCR patients. Therefore, we aim to explore factors associated with tumor recurrence in this patient population.MethodsA total of 1,913 patients diagnosed with breast cancer between 1995 and 2020 and received NAC were included in this analysis. Clinicopathological data of the patients were retrospectively collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This ranking indicates that the HER2-negative population, which includes the triple-negative patients, is mostly associated with increased risk for five-year recurrence. It also shows that patients with HER2-positive expression before neoadjuvant therapy have a better prognosis, which is consistent with findings in prior publications [ 44 , 45 ]. One possible explanation for this is the anti-HER2 targeted therapy that became part of the standard of care in recent years [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…This ranking indicates that the HER2-negative population, which includes the triple-negative patients, is mostly associated with increased risk for five-year recurrence. It also shows that patients with HER2-positive expression before neoadjuvant therapy have a better prognosis, which is consistent with findings in prior publications [ 44 , 45 ]. One possible explanation for this is the anti-HER2 targeted therapy that became part of the standard of care in recent years [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, our study stopped at the primary outcome of complete pathological response due to limited data. As for the prognostic outcome, Asaoka 61 and Xie 62 reached a consensus that cN(+) was found to be the most significant predictor of cancer recurrence in patients with acquired breast pCR. Besides, cN(+) and HER2-positive subtype were 2 clinicopathological prognostic factors that were significantly associated with unfavorable outcomes in terms of DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, despite the favorable prognostic effect of invasive disease eradication, a few of patients with pCR eventually relapse ( 9 , 10 ). Tumor recurrences are in the range of 10-15% at 5 years from surgery, as reported in the large pooled analysis of German Breast Group neoadjuvant studies on 2188 patients ( 41 ), and from a recent meta-analysis on 5748 patients ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of additional treatments in HER2-positive breast cancer patients not achieving a pCR after neoadjuvant therapy is being investigated in several studies ( 6 ), and has been reported as beneficial by the KATHERINE trial ( 7 ). Noteworthy, not all patients with an incomplete tumor response to neoadjuvant therapy relapse - two third of them are indeed disease-free at five years from surgery ( 8 ) - while up to 20% of patients who achieve a pCR eventually recur ( 9 ). This creates uncertainty, and calls into question the prognostic relevance of pCR.…”
Section: Introductionmentioning
confidence: 99%